Solving DSGE portfolio choice models with asymmetric countries - Grzegorz R. Dlugoszek (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
This paper proposes a combination of bifurcation methods and nonlinear moving average as a tool to solve asymmetric DSGE models with portfolio choice. Its performance is compared to the workhorse routine developed by Devereux and Sutherland (2010, 2011). The proposed technique has two advantages. First, it captures the direct effect of uncertainty on portfolio holdings. Second, it reflects the presence of asymmetries by yielding risk adjusted asset positions that lie close to the ergodic mean of the global solution. In terms of Euler equation errors, the proposed method is shown to be on average at least as good as the standard approach.
Keywords: E44; F41; G11; 330; Country Portfolios; Solution Method; Asymmetric Countries